Theoretical framework of green and blue spaces towards enhancing well-being for individuals with hoarding disorder / Wan Mohammad Zaeim Wan Mahadi ... [et al.] - Wan Mahadi, Wan Mohammad Zaeim; Ali Ariff, Azlan Ariff; Mohamed Rafie, Muhammad Firdaus; Ali Ariff, Nor Alisya Afifi; Shafie, Nur Zawani (UiTM Press, 2025)
Hoarding disorder (HD) presents a unique set of challenges that call for novel therapeutic approaches. These approaches incorporate both psychological and environmental aspects, particularly with regard to the planning of green and blue spaces. The concept of green and blue spaces presents a significant opportunity in specific exploration for individuals who are struggling with HD. The aim of this study is to establish the ideation of environments that are conducive to the enhancement of therapeutic interventions, promotion of emotional recovery, and the encouragement of behavioural changes in individuals with HD. By drawing inspiration from the principles of biophilic design and attachment theory, this approach successfully combines natural elements, sensory engagement, and restorative architectural interventions in a harmonious blend. This research employs a two-stage methodology, which consists of conducting site-specific analyses of low-cost housing locations in Kuala Lumpur (PPR Beringin and PPR Desa Tun Razak) through field surveys, observations, and a review of the previously published literature. Attachment theory, cognitive behavioural therapy, and the principles of biophilic design are brought together to develop a theoretical framework. The results show the theoretical incorporation of green and blue spaces into residential settings explores the possibilities to improve psychological well-being. The capacity of the spaces to serve as potential restorative architectural design is brought to light by incorporating concepts from the fields of psychology, architecture, and nature. Future research recommends investigations on both the long-term effects of these therapeutic spaces